(untitled) (Yesterday & Today Journal for History Education in South Africa and abroad, 2021)
The paper reports on research on History student teachers’ enhancement of Work Integrated Learning (WIL) using online tools like a discussion board and blogs. It draws on the enhancement programme planned for the History student teachers – 78 Bachelor of Education students (BEd) 4th-year students and 28 Post-Graduate Certificate in Education (PGCE) students who were expected to integrate technological tools in their teaching during WIL; some of them, mostly PGCE students lacked the necessary Pedagogical Content Knowledge (PCK) in this regard. Thus, the main purpose of this study was to explore the extent to which the online discussion board and blogs enhanced student teachers’ classroom practice during WIL. The theoretical lens that informed this study was the five-factor model of mentoring for effective teaching that underpinned the need for improved support and mentoring by the History student teachers: personal attributes, system requirements, pedagogical knowledge, modelling, and feedback. Qualitative research methods and purposive sampling were used. The data was analysed using content analysis as per the five-factor model of mentoring for effective teaching. The findings revealed that student teachers responded overwhelmingly positively to the use of the online tools. They also revealed that the one-and-a-half-hour face-to-face debriefing was not acceptable to the majority of the participants. Most of them felt that it was just a formality and failed to address their immediate needs compared to being mentored online by their peers. In light of these findings, the study suggests that the usage of an online discussion board and blogs in mentoring and encouraging the improvement of student teachers’ PCK should be considered and included when planning WIL programmes.